Development and validation of a radiological diagnosis model for hypersensitivity pneumonitis. Issue 2 (16th August 2018) - Salisbury, Margaret L.; Gross, Barry H.; Chughtai, Aamer; Sayyouh, Mohamed; Kazerooni, Ella A.; Bartholmai, Brian J.; Xia, Meng; Murray, Susan; Myers, Jeffrey L.; Lagstein, Amir; Konopka, Kristine E.; Belloli, Elizabeth A.; et al.
High-resolution computed tomography (HRCT) may be useful for diagnosing hypersensitivity pneumonitis. Here, we develop and validate a radiological diagnosis model and model-based points score. Patients with interstitial lung disease seen at the University of Michigan Health System (derivation cohort) or enrolling in the Lung Tissue Research Consortium (validation cohort) were included. A thin-section, inspiratory HRCT scan was required. Thoracic radiologists documented radiological features. The derivation cohort comprised 356 subjects (33.9% hypersensitivity pneumonitis) and the validation cohort comprised 424 subjects (15.5% hypersensitivity pneumonitis). An age-, sex- and smoking status-adjusted logistic regression model identified extent of mosaic attenuation or air trapping greater than that of reticulation ("MA-AT>Reticulation"; OR 6.20, 95% CI 3.53–10.90; p<0.0001) and diffuse axial disease distribution (OR 2.33, 95% CI 1.31–4.16; p=0.004) as hypersensitivity pneumonitis predictors (area under the receiver operating characteristic curve 0.814). A model-based score >2 (1 point for axial distribution, 2 points for "MA-AT>Reticulation") has specificity 90% and positive predictive value (PPV) 74% in the derivation cohort and specificity 96% and PPV 44% in the validation cohort. Similar model performance is seen with population restriction to those reporting no exposure (score >2: specificity 91%). When radiological mosaic attenuation or air trapping are more extensive than reticulation and disease has diffuse axial distribution, hypersensitivity pneumonitis specificity is high and false diagnosis risk low (<10%), but PPV is diminished in a low-prevalence setting. When HRCT shows more mosaic attenuation than reticulation and diffuse axial ILD, false hypersensitivity pneumonitis diagnosis risk is <10% http://ow.ly/tthG30k3Vj2